Side effects associated with psychotropic medications in patients with bipolar disorder: evidence from two independent samples. (July 2013) - Serretti, Alessandro; Chiesa, Alberto; Calati, Raffaella; Fabbri, Chiara; Sentissi, Othman; De Ronchi, Diana; Mendlewicz, Julien; Souery, Daniel
Available evidence concerning the side effects experienced by bipolar disorder (BD) patients under naturalistic conditions has been poorly investigated. The aim of this study was therefore to investigate side effects related to major psychotropic drugs in two independent samples of BD patients naturalistically treated with mood stabilizers, antidepressants, antipsychotics and/or anxiolytics. Overall, 3654 patients from the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) sample and 282 patients from the Clinical Outcome and Psycho-Education for Bipolar Disorder (COPE-BD) sample were included. The primary outcome measure was the influence of each class of psychotropic drugs under investigation on the emergence of any side effect, as measured with the monitoring form in the STEP-BD study and the Udvalg for Kliniske Undersøgelser Side Effect Rating Scale in the COPE-BD study. Secondary outcome measures included the effects of such drugs on psychic, neurologic, autonomic and other side effects. Mood stabilizers and antipsychotics were associated with high rates of side effects in both samples. Furthermore, antipsychotics were specifically associated with psychic side effects, whereas mood stabilizers were specifically associated with neurologic side effects. Our results largely confirm in a naturalistic setting results previously observed in randomized controlled trials focusing on BD patients.